Technological characteristics of pre- and post-rigor deboned beef mixtures from Holstein steers and quality attributes of cooked beef sausage. (November 2018) - Sukumaran, Anuraj T.; Holtcamp, Alexander J.; Campbell, Yan L.; Burnett, Derris; Schilling, Mark W.; Dinh, Thu T.N.
Abstract: The objective of this study was to determine the effects of deboning time (pre- and post-rigor), processing steps (grinding - GB; salting - SB; batter formulation - BB), and storage time on the quality of raw beef mixtures and vacuum-packaged cooked sausage, produced using a commercial formulation with 0.25% phosphate. The pH was greater in pre-rigor GB and SB than in post-rigor GB and SB ( P < .001). However, deboning time had no effect on metmyoglobin reducing activity, cooking loss, and color of raw beef mixtures. Protein solubility of pre-rigor beef mixtures (124.26 mg/kg) was greater than that of post-rigor beef (113.93 mg/kg; P = .071). TBARS were increased in BB but decreased during vacuum storage of cooked sausage ( P ≤ .018). Except for chewiness and saltiness being 52.9 N-mm and 0.3 points greater in post-rigor sausage ( P = .040 and 0.054, respectively), texture profile analysis and trained panelists detected no difference in texture between pre- and post-rigor sausage.